Potable water use of residential consumers in the Cape Town metropolitan area with access to groundwater as a supplementary household water source - Wright, T.; Jacobs, H.E. (Water S. A., 2016)
The potable water use recorded by 3 579 residential consumer water meters in Cape Town, South Africa, was analysed as part of this research. The focus was on selected residential properties in serviced areas, with additional private access to groundwater as a supplementary household water source. Private consumers in South Africa are not normally required to report on, or meter, groundwater use. The research team analysed records of an extensive, compulsory registration process for supplementary on-site water sources that was introduced by the City of Cape Town during the prolonged drought between 2004 and 2005. The main objective of this research was to determine the average annual water demand of residential properties serviced via the potable water distribution system, with additional registered access to a supplementary on-site groundwater source. Geo-referencing was employed to determine the approximate coordinate of each property, with subsequent one-by-one verification of each address. The data set initially contained 4 487 properties, but after filtering and verification 3 579 consumers remained in the data set for further analyses. The unique property code was identified for each verified property in order to link the attributes of consumers with access to on-site groundwater sources to their corresponding water meter records, so that the potable water demand for these stands could be analysed. The annual average water demand of the properties was subsequently obtained and analysed for two separate periods, namely, 2010 and 2014. The water use, categorised according to stand size, was similar for both periods. The results showed that consumers with access to groundwater used only about 65% of the estimated average annual water demand when compared to applicable water demand guidelines.